Implementasi Penghitung Laju Respirasi pada Sistem Polisomnografi menggunakan Mikrofon dan Arduino Nano - Martin Clinton Tosima Manullang; Nova Resfita (LPPM STT Terpadu Nurul Fikri, 2021)
Sleep apnea is a severe sleep disorder leading to severe threats such as heart attacks, strokes, diabetes, kidney failure, hypertension, etc. Not only is the diagnosis of sleep apnea a challenging measure, but it also requires a high cost of equipment, the limitations of available tools, and becomes a complicated diagnosis operated personally at home. Using the microphone embedded in the Arduino Nano, a system to measure the respiratory rate develops as a minor part of the sleep apnea diagnostic system using polysomnography. A filtering system is attached to eliminate noise and environmental consequences around the observation site. This prototype evaluates by comparing the output value with the manual calculation of the respiratory rate. Of the trials executed, the achieved system accuracy in counting the respiratory rate is above 93%, meaning that this prototype system is ideal as a method of measuring the respiratory rate.